Książka jako przestrzeń spotkania, rozmowy i uważności. Wrażeniowe czytanie tekstów literackich .......... 81 - Swędrowska, Małgorzata (Skąd się biorą czytelnicy?, 2025)
A BOOK AS A SPACE OF ENCOUNTER, CONVERSATION AND MINDFULNESS: IMPRESSIONISTIC READING OF LITERARY TEXTSImpressionistic reading is one of the ways of connecting with children. A book may be an opportunity for an encounter, allowing one to talk about oneself on top of the literary text, discuss how we perceive the world around us, how we define words, and how we notice contexts. Impressionistic reading is a helpful method in running reading workshops that serves to warm the hearts of readers, both young and old, to books and invite them to enter the world of literature.